(3QSGdI aj GdehVhYGJs - (3GdgeOGfj, YHO GdUeO, J (B1216 (3g`s
(3ChdgG (B:s
... (3bGd aj GdJMQjQ haj GdTQY eYghOI ebJQfI HMQcGJ hScfGJ eNUhUI JGQI jJbQH HgG Edi Gddg JYGdi bGd aj (B.. (3haj GdTQY YHGQI Yf YHGQI eNUhUI JGQI jchf PcQG eNJUG cGdUdGI HGdJSHjM (B...s
(3BNQgG (B:s
... (3ade jcaj ddeJTQYI MbjbI eJabI MJi jSJfHW efgG GdTQYjI fYe jecf Cf jbGd Gf KGHJ YfO GdeJTQYI Cf gPg GdCdaGX eSJYedI aj GdeYfi GdLOjO hefbhdI YfOge ef GdeYGfj (B..(3Jes
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf (B2\154s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
(3Qbej ZjQ edhfs
Keywords: (3CUhd Gdabgs